Moral Values and Hypocrisy in Nathaniel Hawthorne’s "The Scarlet Letter": A Literary Analysis - Sikder, Liton Baron (International Journal of Applied and Scientific Research, 2024)
This research paper provides a comprehensive analysis of Nathaniel Hawthorne’s The Scarlet Letter, focusing on its portrayal of moral values and hypocrisy. It examines how literature mirrors societal life and imparts moral lessons, delving into the novel’s thematic intricacies, character developments, and narrative techniques. The study highlights the contrasting spectrum of moral values depicted in the story, encompassing both positive virtues and negative traits. Through meticulous examination, it underscores the educational value of literature, suggesting that engaging with literary works fosters critical thinking and moral development. Additionally, the paper discusses the broader implications of incorporating literature into education, emphasizing its potential to enhance language skills, vocabulary acquisition, and moral understanding. By analysing the moral dynamics and character portrayals in The Scarlet Letter, the research offers insights into how literature can serve as a tool for understanding and navigating complex moral landscapes. It proposes that literature, by reflecting and critiquing societal norms and behaviours, can be an essential component in education, aiding in the development of both intellectual and ethical faculties.